Magnetic fields and electrical fields are not invisible fields but mechanical waves in the space fabric structure, unified theory of gravity and magnetism, Definition of space fabric from Al Quran, space fabric mechanics: المجالات المغناطيسية والكهربية ليست مجالات خفية ولكنها موجات ميكانيكية في بناء الفضاء، نظرية موحدة لتفسير قوى الجاذبية والقوة الكهرومغناطيسية، تعريف بناء الزمكان من القرآن الكريم، ميكانيكا السماء - Ahmed Mohamed Atteya, (Journal of engineering sciences and information technology, 2021)
One of the fundamental forces in nature is the electromagnetic force which is responsible for attraction and repulsion forces between charged particles, electrical and magnetic field and electromagnetic waves and this force is consider until now invisible force and do not need medium, I introduce this research for show new theory of electromagnetism and it flow throw space time fabric and finally relate it with general relativity theory that illustrate gravity force, we will show in research that all electromagnetic phenomena forms in the space time fabric structure and it is not invisible, we start that by prove new space time fabric physical property with matter interaction that the fabric resist matter speed in it, thus any accelerated particle will produce wave follow it in space time fabric, and then we redefine space fabric and it is not vacuum but medium like matter and Allah created it matter but without separation between its particles and it is smoothed and even and Allah mention this information in many phrases in Al quran Al kareem and it name is Asmaa structure, and according to that we will re understand electromagnetism, electron has very fast spinning movement in asmaa this will create circular wave in asmaa around electron as it resist matter speed, this wave is real mechanical wave that has force, if another electron get near the first their waves will move them away from each other this called now repulsion force between electron similar negative charge, we then move to atom where it nucleus contain protons and neutrons and each contain three elementary particles called quarks, each quark has spin movement and will make circular wave around each one in asmaa, but quarks are close together by nuclear fore which is bigger than their waves repulsion thus their waves will combined making big circular waves in asmaa around nucleus which known now as atom energy level, electrons rotate in these atomic waves and as the electron has its own circular wave while orbiting nucleus thus electron wave strength direction will be in the attraction direction from outside to the inside of atom for near electrons and atoms and this known now as atom has positive charge, so atom positive charge do not came from proton but from unpaired electrons in orbits, if we have direct current of electrons wire all their huge electron waves number will add together as they move similarly in same direction and make big circular real waves around wire in asmaa this is called now magnetic fields, and if we make this current of electron in wire alternative current so electron will move up and down making their waves move up and down and due to asmaa physical properties this disturbance in asmaa will make transverse wave in asmaa structure moving away from wire with fixed speed depend on medium properties and this is called now electromagnetic waves and we will also illustrate special relativity experiment in concept that asmaa resist particles speed that make every electrons and particles normal speed moving in clock moving in speedy plane decrease making its clock to slow down not time itself slow down and after I draw the hole theory I discover that Maxwell hypothesis for drawing his equations foe electromagnetism match exactly our results.